Biochemical and Genetic Approaches Improving Nitrogen Use Efficiency in Cereal Crops: A Review - Sandhu, Nitika; Sethi, Mehak; Kumar, Aman; Dang, Devpriya; Singh, Jasneet; Chhuneja, Parveen (Frontiers in Plant Science, 2021)
Nitrogen is an essential nutrient required in large quantities for the proper growth and development of the plant. Nitrogen is the most limiting macronutrient for crop production in most of the world’s agricultural areas. The dynamic nature of nitrogen and its tendency to lose soil and environment systems create a unique and challenging environment for its proper management. Exploiting genetic diversity, developing nutrient efficient novel varieties with better agronomy and crop management practices combined with improved crop genetics have been significant factors behind increased crop production. In this review, we highlight the various biochemical, genetic factors and the regulatory mechanisms controlling the plant nitrogen economy necessary for reducing fertilizer cost and improving nitrogen use efficiency while maintaining an acceptable grain yield.